2011
DOI: 10.1111/j.1447-0756.2011.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary postpartum hemorrhage due to uterine artery pseudoaneurysm rupture in von Willebrand disease

Abstract: We here report a case of a 33-year-old woman who experienced secondary postpartum hemorrhage (PPH) due to uterine artery pseudoaneurysm rupture. She had intrauterine balloon tamponade for unexplained primary PPH after spontaneous vaginal delivery, and subsequent angiography showed no abnormal contrast extravasation. However, profuse vaginal bleeding occurred 22 days postpartum. Color Doppler ultrasonography demonstrated an anechoic mass with turbulent flow in the lower uterine segment, corresponding to uterine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, it is possible that uterine arteries may have some abnormalities, or at least vulnerability to D&C. In addition, the presence of coagulopathy and/or hemorrhagic diathesis (Kasabach–Merritt syndrome) may have contributed to the occurrence of UAP; the strength of the vasculature requires intact coagulation factors. Indeed, some previous reports have indicated that underlying disorders were present and contributed to the occurrence of pseudoaneurysm: coagulopathy/hemorrhagic diathesis (von Willebrand disease) [3] and vascular abnormalities (Ehlers–Danlos syndrome) [4], which coexisted in the present patient.…”
Section: Conflict Of Interestmentioning
confidence: 49%
“…However, it is possible that uterine arteries may have some abnormalities, or at least vulnerability to D&C. In addition, the presence of coagulopathy and/or hemorrhagic diathesis (Kasabach–Merritt syndrome) may have contributed to the occurrence of UAP; the strength of the vasculature requires intact coagulation factors. Indeed, some previous reports have indicated that underlying disorders were present and contributed to the occurrence of pseudoaneurysm: coagulopathy/hemorrhagic diathesis (von Willebrand disease) [3] and vascular abnormalities (Ehlers–Danlos syndrome) [4], which coexisted in the present patient.…”
Section: Conflict Of Interestmentioning
confidence: 49%
“…According to a prospective study, failure of thrombosis was associated with considerably large PAs and the concomitant use of anticoagulation or antiplatelet agents [6]. Furthermore, late postpartum hemorrhage due to ruptured PA also occurs in patients with von Willebrand disease [7,8]. In general, PAs are thrombosed spontane-ously.…”
Section: Discussionmentioning
confidence: 99%
“…In general, PAs are thrombosed spontane-ously. Therefore, PA is formed as a result of repeated bleeding and thrombus due to abnormal hemostasis [4][5][6][7][8]. Hence, an underlying bleeding disorder or anticoagulation therapy should be considered in patients presenting with PA rupture-induced postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A UAP appears as a saclike structure within the uterus with a connection to the uterine artery. 23,25,26 Conservative treatment may be to monitor the pseudoaneurysm if it has not ruptured, because pseudoaneurysms have been reported to resolve spontaneously. 27 Rupture is prone to occur if the UAP diameter exceeds 2 cm.…”
Section: Discussionmentioning
confidence: 99%